Behavior of Tourism Industry under the Situation of Environmental Threats and Carbon Emission: Time Series Analysis from Thailand - Jermsittiparsert, Kittisak; Chankoson, Thitinan (International Journal of Energy Economics and Policy, 2019)
The purpose of this study is to examine the environmental trend of tourism industry in the region of Thailand. For this objective, six dimensions for tourism and five for carbon emission as environmental factor is observed. Time duration of the study consists of 2000 to 2014 with annual observations. Data is collected from official webpage of world development indicator for the regression analysis. Findings of the study indicate that carbon emission through manufacturing and construction industries and carbon emission from other sector has their significant impact on tourism industry in Thailand. These findings are providing reasonable evidence for their regional and managerial implication as significant attention is required to control the harmful effect of environmental indicators on tourism industry. In addition, practical implication of the study can be expanded to other economies in ASEAN region like Malaysia and Indonesia as well. However, limitations of the study can be considered through considering of only one dimension of environmental factor (carbon emission), while ignoring others. Meanwhile, study is limited to the contemporary time duration and application of advance econometric techniques. Future studies can be reconsidered while overcoming these limitations. Keywords: environmental factors, carbon emission, tourism industry, World Bank, Thailand JEL Classifications: Q55, Z31 DOI: https://doi.org/10.32479/ijeep.8365